2007
DOI: 10.1055/s-2007-981524
|View full text |Cite
|
Sign up to set email alerts
|

Red American Ginseng: Ginsenoside Constituents and Antiproliferative Activities of Heat-Processed Panax quinquefolius Roots

Abstract: Red Asian ginseng ( Panax ginseng C. A. Meyer, Araliaceae) is used in many Oriental countries. In this study, the saponin constituents and anticancer activities of steamed American ginseng ( Panax quinquefolius L.) roots were evaluated. The contents of 12 ginsenosides in the roots were determined using high performance liquid chromatography (HPLC). After the steaming treatment (100 - 120 degrees C for 1 h and 120 degrees C for 0.5 - 4 h), the quantity of 7 ginsenosides decreased and that of 5 others increased.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
139
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 166 publications
(151 citation statements)
references
References 16 publications
(13 reference statements)
8
139
0
1
Order By: Relevance
“…The capacity of various concentrations of Rg1 inhibited cell proliferation of TF-1/Epo acute myelogenous leukemia cell lines in a dose and time-dependent manner ( Figure 1A, B). These antiproliferative activities were agreement with previous study that Rg1 has been suggested to inhibit human cancer cell growth (Wang et al, 2007;Li et al, 2008). Apoptosis is the most common way that anti-tumor medicine induces cell death.…”
Section: Discussionsupporting
confidence: 93%
“…The capacity of various concentrations of Rg1 inhibited cell proliferation of TF-1/Epo acute myelogenous leukemia cell lines in a dose and time-dependent manner ( Figure 1A, B). These antiproliferative activities were agreement with previous study that Rg1 has been suggested to inhibit human cancer cell growth (Wang et al, 2007;Li et al, 2008). Apoptosis is the most common way that anti-tumor medicine induces cell death.…”
Section: Discussionsupporting
confidence: 93%
“…Our group found that after the steam treatment of American ginseng, the antiproliferative effects on cancer cells were improved significantly possibly due to the altered ginsenoside profile. 11,13) Recently, we analyzed the ginsenoside content in different American ginseng plant parts using HPLC in our laboratories. 14,31) It was found that different plant parts possessed different ginseng saponin composition, and American ginseng berry had a distinct ginsenoside profile compared to other plant parts.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] In oriental countries, Asian ginseng root can be steamed to produce red ginseng, the pharmacological effects, such as the anticancer activity, of red ginseng are stronger than that of unsteamed ginseng. 10,11) Another species in the Panax genus, American ginseng (Panax quinquefolius L.), has gained popularity with the American public in the past decade, 7,12) however since most studies have focused on the root of Asian ginseng, there is limited data available with regard to the cancer preventive potential of American ginseng.We evaluated the cancer chemopreventive activities of American ginseng root extract on human colorectal and breast cancer. 11,13) It is believed that the bioactive constituents in American ginseng are ginsenosides.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, fresh ginseng is processed into red ginseng or black ginseng through the process of steaming and drying or processed into white ginseng by a simple drying process [12]. These processing methods increase their pharmacological effects and decrease their cytotoxicity through the chemical alteration of components and the content change [13]. Thus, recent many studies have examined the enhancement of active components and physiological activites by fermenting ginseng.…”
Section: Introductionmentioning
confidence: 99%